2015
DOI: 10.1016/j.chom.2015.01.014
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Scale Vector Resource Enables High-Throughput Reverse Genetic Screening in a Malaria Parasite

Abstract: SummaryThe genome-wide identification of gene functions in malaria parasites is hampered by a lack of reverse genetic screening methods. We present a large-scale resource of barcoded vectors with long homology arms for effective modification of the Plasmodium berghei genome. Cotransfecting dozens of vectors into the haploid blood stages creates complex pools of barcoded mutants, whose competitive fitness can be measured during infection of a single mouse using barcode sequencing (barseq). To validate the utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
147
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(155 citation statements)
references
References 50 publications
(68 reference statements)
3
147
0
Order By: Relevance
“…These two clones must have arisen from a double crossover recombination event in a population of parasites harboring a duplicated copy of fh. Although parasites with gene duplication are thought to be unstable, the existence of duplication has been noted earlier in the case of rio2 (37) and dhodh (38). The variation in the genotype across the 17 clones that we have obtained shows that the parasites have not multiplied from a single wrong event of homologous recombination.…”
Section: Essentiality Of Fumarate Hydratase For Psupporting
confidence: 69%
“…These two clones must have arisen from a double crossover recombination event in a population of parasites harboring a duplicated copy of fh. Although parasites with gene duplication are thought to be unstable, the existence of duplication has been noted earlier in the case of rio2 (37) and dhodh (38). The variation in the genotype across the 17 clones that we have obtained shows that the parasites have not multiplied from a single wrong event of homologous recombination.…”
Section: Essentiality Of Fumarate Hydratase For Psupporting
confidence: 69%
“…It is likely that strong positive selection approaches will be the most immediately rewarding, such as selecting for mutants with increased resistance (Pradhan et al 2015) or with the ability to survive environmental stresses such as heat shock. There are two fundamental approaches to performing such screens, either using pools of pre-existing mutants with known insertion sites ("parallel phenotyping") (Gomes et al 2015), or by generating new pools for every screen by transfection. Until transposon insertion efficiency is radically improved, the latter approach will be limited, but initial data reported here monitoring growth of up to 128 previously generated mutants in a single pool suggest that the parallel phenotyping approach is immediately tractable.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach known as parallel phenotyping would create pools of pre-existing P. falciparum clones with known piggyBac insertion sites, similar to an approach that is now possible using targeted gene modification in Plasmodium berghei (Gomes et al 2015). This approach has the advantage that it can be carried out using a validated library of piggyBac clones rather than generating a new pool every time.…”
Section: Parallel Phenotype Analysis Of Mutant Parasite Poolsmentioning
confidence: 99%
“…The PlasmoGem knockout screen database (http://plasmogem.sanger.ac.uk/phenotyp es; Bushell et al, 2017;Gomes et al, 2015) was searched for the P. berghei homologues of the P. falciparum phospholipases in order to evaluate if these are essential for the erythrocytic replication cycle. Analyses of the blood-stage growth phenotypes revealed that 14 of the putative phospholipases were predicted to be dispensable for erythrocytic replication, while PI-PLC (PBANKA_1013500) and the putative PLA 2 (PBANKA_135800) were determined to be essential with significantly reduced relative growth rates (Table 2).…”
Section: Phospholipases Of Plasmodial Parasitesmentioning
confidence: 99%